Correlation analysis of vibration modes in physical vapour deposited Bi2Se3 thin films probed by the Raman mapping technique. Issue 22 (8th October 2021) - Niherysh, K. A.; Andzane, J.; Mikhalik, M. M.; Zavadsky, S. M.; Dobrokhotov, P. L.; Lombardi, F.; Prischepa, S. L.; Komissarov, I. V.; Erts, D.
Abstract : We propose the evaluation of strain in Bi2 Se3 films based on the correlation analysis of in-plane (E2g) and out-of-plane (A21g) Raman mode positions as well as the algorithm of phonon deformation potential calculation for biaxial in-plane strain. Abstract : In this work, the Raman spectroscopy mapping technique is used for the analysis of mechanical strain in Bi2 Se3 thin films of various (3–400 nm) thicknesses synthesized by physical vapour deposition on amorphous quartz and single-layer graphene substrates. The evaluation of strain effects is based on the correlation analysis of in-plane (E2g) and out-of-plane (A21g) Raman mode positions. For Bi2 Se3 films deposited on quartz, experimental datapoints are scattered along the line with a slope of ∼0.85, related to the distribution of hydrostatic strain. In contrast to quartz/Bi2 Se3 samples, for graphene/Bi2 Se3 heterostructures with the same thicknesses, an additional negative slope of ∼−0.85, which can be associated with the distribution of the in-plane ( a – b ) biaxial tensile strain due to the film–substrate lattice mismatch, is observed. The algorithm of phonon deformation potential (PDP) calculation based on the proposed strain analysis for the 3 nm thick Bi2 Se3 film deposited on the graphene substrate, where the strain is considered to be coherent across the thickness, is demonstrated. The PDPs for biaxial in-plane strain of the Bi2 Se3 3 nm film in in-plane and out-of-plane modes are equal to −7.64 cm −1 /% and −6.97 cm −1 /%, respectively.